A Review on Region Detection And Matching For Object Recognition (International Journal of Engineering and Computer Science, 2014)
Object Recognition is based on Objective and Subjective dimensions where the objectivity is guided by the parameters like colour, texture, shape, size and scale whereas the subjectivity is guided by the perception and cognition of the image interpreters .In this paper we aim to study various object recognition method based on region detection and matching. The motivation is to search and propose a method which can obtain the similar and significant objects in different images with the best accuracy and in less execution time.